SIAPA PEMBUNUHNJA: ROMAN DETEKTIF KARYA JOESOEF SOU’YB - Atisah Atisah (JENTERA: Jurnal Kajian Sastra, 2015)
This writing was intended to analyze Siapa Pembunuhnya by Joesoef Sou’yb. The analysis was focused on the murder characters that also became the problem of the story. The approach used was detective story theory in Apsanti’s books, while the method used was analysis-descriptive method. In 1930s, Joesoef Sou’yb was very famous as a detective stories author. The story Siapa Pemboenoehnja was one of his works in which in it were murder problems filled with riddles. Complicatedand full of surpriseplot accompanied by supporting background description made readers curious wanting to know the end of the story. It showed the skill of the author in creating a story